The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/eve.13716
|View full text |Cite
|
Sign up to set email alerts
|

Standing osteosynthesis of an accessory carpal bone fracture in a Warmblood mare with a 6‐hole 3.5 talonavicular fusion plate and 3.5‐mm screws

Abstract: A 9-year-old Warmblood, high-level showjumping mare sustained an acute, closed, vertical, comminuted fracture of the left accessory carpal bone (ACB) during a fall. The fracture was repaired under standing sedation and local anaesthesia, using a 6-hole APTUS® 3.5 TFP and 5 × 3.5-mm selftapping TriLock© screws. The mare recovered from surgery without complications. Upon follow-up examination 9 months post-operatively the mare was sound in all gaits and back to full athletic activity. The ACB fracture had comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The case report by Aßmann et al (2023) in this issue reported the surgical management of an accessory carpal bone fracture, repaired under standing sedation. This sets the tone for the debate between the risks and benefits of standing sedation versus general anaesthesia in horses undergoing fracture repair.…”
mentioning
confidence: 98%
“…The case report by Aßmann et al (2023) in this issue reported the surgical management of an accessory carpal bone fracture, repaired under standing sedation. This sets the tone for the debate between the risks and benefits of standing sedation versus general anaesthesia in horses undergoing fracture repair.…”
mentioning
confidence: 98%